Karakterisasi Dan Keanekaragaman Tumbuhan Famili Arecaceae Di Kampus 1 UIN Sunan Gunung Djati Bandung - Devi Novianti; Dina Nursaidah; Ateng Supriatna (Jurnal Riset Rumpun Ilmu Tanaman, 2023)
Natural resources are the main component in building a biological culture system in the span of the earth. Efforts to manage natural resources, especially plants, are characterized by utilization according to their characteristics. The Arecaceae family (palm) belongs to the plant family of the oldest among flowering plants. This research was conducted through an exploratory survey on plants of the Arecaceae family in the area of Campus 1, Sunan Gunung Djati State Islamic University, Bandung. There were nine plant species found with a total number of individuals of all species totaling 148. The diversity index of palm plants in the Campus I area of UIN Sunan Gunung Djati Bandung obtained a result of 1.59. The utilization of Arecaceae plants is very diverse for each organ, namely fruits, roots, flowers, leaves, roots, and stems which are divided into five categories of needs, food sources, traditional medicines, building materials, handicrafts, and other uses.